A setting for generalized orthogonalization - Corach, Gustavo (2014)
Let H be a complex Hilbert space. We study the geometry of the space of pairs (A,E), for A a (semidefinite bounded linear) positive operator on H and E a (bounded linear) projection on H such that AE = E*A.